Key Audit Matters and earnings management practice pre and during COVID-19: evidence from Jordan - Alshdaifat, Sajead Mowafaq; Abdul-Hamid, Mohamad Ali; Alhadab, Mohammad; Fauzi Saidin, Saidatunur; Ab Aziz, Noor Hidayah (Emerald Publishing, 2025)
Purpose: This study examines the association between ISA 701 of Key Audit Matters (KAM) with accrual and real earning management practices pre and during the COVID-19 pandemic in Jordanian Industrial listed firms. Design/methodology/approach: The content analysis method was utilized with longitudinal data derived from the annual reports of industrial firms listed on the Amman Stock Exchange with 240 firm-year observations for the period of pre and during COVID-19 (2017–2021). Findings: The inability of auditors to detect earnings management through KAM is evident in the results, as they reveal a positive association between KAM and real earnings management through abnormal cash flows from operations pre COVID-19 period. Additionally, during the COVID-19 pandemic, earnings manipulation is observed to increase, particularly through abnormal levels of production costs. This result highlight that managers may participate in earning management in areas not covered by the auditor in KAM report to meet their target. Practical implications: The findings assist regulatory bodies in their oversight and management of the auditing. In addition, the findings may help standard setters, regulators and the auditing profession as they evaluate the challenges within an unpredictable economic environment. Originality/value: This is the first comparative study that evaluates the association between KAM and earnings management in the period of pre and during COVID-19. In the context of emerging economies, characterized by distinct corporate governance frameworks, this study enables the establishment of initial assumptions regarding the KAM reporting status of pre and during COVID-19.